Secondary battery and electronic device

By doping alloy element A in the positive electrode current collector of the secondary battery and adjusting the lithium salt composition in the electrolyte, the shortcomings of the secondary battery in both cycling and rate performance are solved, and better battery performance and longer service life are achieved.

CN119864487APending Publication Date: 2025-04-22NINGDE AMPEREX TECHNOLOGY LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510080266.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Existing secondary batteries have shortcomings in taking into account both cycling performance and rate-to-rate performance, especially lithium-ion batteries are prone to positive current collector corrosion during high-rate charging and discharging, resulting in a degradation of cycling performance.

Method used

By doping alloy element A (such as Fe, Si, Ti or V) in the positive electrode current collector, and mixing lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate in the electrolyte, the mass ratio is controlled to the mass percentage of alloy element A, and specific conditions are met to increase the strength of the positive electrode current collector and reduce the corrosion effect of the electrolyte on it.

Benefits of technology

It achieves a better balance between cycle performance and rate performance of the secondary battery, improves the overall performance of the battery, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005248564860000021
    Figure BDA0005248564860000021
  • Figure BDA0005248564860000031
    Figure BDA0005248564860000031
  • Figure BDA0005248564860000041
    Figure BDA0005248564860000041
Patent Text Reader

Abstract

The invention provides a secondary battery and electronic equipment, the secondary battery comprises a positive pole piece and an electrolyte, the positive pole piece comprises a positive current collector and a positive active material layer arranged on at least one surface of the positive current collector, the positive current collector comprises a metal element Al and an alloy element A, the alloy element A comprises at least one of Fe, Si, Ti or V, and the metal element Al and the alloy element A are arranged on the surface of the positive current collector. Based on the mass of the positive electrode current collector, the mass percentage content of the alloy element A is a%, and a is greater than or equal to 0.001 and less than or equal to 1; the electrolyte comprises lithium salt, the lithium salt comprises bis (fluorosulfonyl) lithium imide and lithium hexafluorophosphate, the mass ratio of the bis (fluorosulfonyl) lithium imide to the lithium hexafluorophosphate is b, and b / a is larger than or equal to 0.2 and smaller than or equal to 20000. And the secondary battery has relatively good cycle performance and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a secondary battery and an electronic device. Background Art

[0002] Secondary batteries represented by lithium-ion batteries are widely used in digital electronic products, energy storage, drones, power tools, electric vehicles and other products due to their high energy density, long cycle life, high safety, fast charging capability and other characteristics. With the widespread application of secondary batteries, higher requirements are placed on the performance of secondary batteries, so it is necessary to provide a secondary battery that takes into account both cycle performance and rate performance. Summary of the invention

[0003] The present application provides a secondary battery and an electronic device, wherein the secondary battery can better balance cycle performance and rate performance.

[0004] In a first aspect, the present application provides a secondary battery, comprising a positive electrode plate and an electrolyte, the positive electrode plate comprising a positive electrode collector and a positive electrode active material layer arranged on at least one surface of the positive electrode collector, wherein the positive electrode collector comprises a metal element Al and an alloy element A, the alloy element A comprises at least one of Fe, Si, Ti or V, and the mass percentage of the alloy element A is a%, 0.001≤a≤1 based on the mass of the positive electrode collector; the electrolyte comprises a lithium salt, the lithium salt comprises lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate, and the mass ratio of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate is b; a and b satisfy: 0.2≤b / a≤20000.

[0005] Based on the present application, the lithium salt in the electrolyte includes lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate. Lithium bis(fluorosulfonyl)imide can effectively improve the rate performance of the secondary battery, but a too high mass ratio of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate will cause corrosion to the positive electrode collector and deteriorate the cycle performance of the secondary battery. By doping a certain content of alloy element A in the positive electrode collector, the strength of the positive electrode collector can be effectively improved, and the influence of the lithium salt in the electrolyte on the positive electrode collector can be reduced. By controlling the mass ratio of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate in the lithium salt and the mass percentage of the alloy element A in the positive electrode collector to meet the above conditions, the secondary battery can have good cycle performance and rate performance.

[0006] In some embodiments, the secondary battery satisfies at least one of the following conditions: (1) 2≤b / a≤4000; (2) 0.005≤a≤0.5; (3) 0.2≤b≤32; (4) based on the mass of the electrolyte, the mass percentage of lithium bis(fluorosulfonyl)imide is 1% to 25%; preferably 3% to 20%. Based on the above embodiments, if at least one of the above conditions is met, the secondary battery has better cycle performance and / or rate performance.

[0007] In some embodiments, the electrolyte further comprises a compound represented by formula (I):

[0008]

[0009] Among them, R 11 The alkyl radical is selected from alkali metals, cyano, substituted or unsubstituted C1 to C6 alkyl, substituted or unsubstituted C2 to C6 alkenyl, substituted or unsubstituted C2 to C6 alkynyl, substituted or unsubstituted C1 to C6 heteroalkyl, the number of heteroatoms in the heteroalkyl is 1 to 5, the heteroatoms in the heteroalkyl are selected from O, N or S, and, when substituted, the substituent is selected from halogen atoms, cyano, C2 to C5 cycloalkyl or C6 to C 12 Based on the above embodiment, further adding the compound represented by formula (I) into the electrolyte can further inhibit the corrosion of the positive electrode current collector by the lithium salt in the electrolyte by forming a dense protective layer on the surface of the positive electrode current collector, thereby synergizing the composition of the lithium salt in the electrolyte and the positive electrode current collector to further improve the cycle performance and rate performance of the secondary battery.

[0010] In some embodiments, the compound represented by formula (I) includes at least one of the following compounds:

[0011] Based on the above embodiments, the use of the above compounds can improve the cycle performance and rate performance of the secondary battery.

[0012] In some embodiments, based on the mass of the electrolyte, the mass percentage of the compound represented by formula (I) is c%, 0.04≤b / c≤20000. Based on the above embodiment, the mass percentage of the compound represented by formula (I) and the mass ratio of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate in the electrolyte are controlled to satisfy the above relationship, which can further improve the cycle performance and rate performance of the secondary battery. Preferably, 0.5≤b / c≤4000.

[0013] In some embodiments, 0.001≤c≤5. Based on the above embodiments, when the mass percentage of the compound represented by formula (I) meets the above range, the cycle performance of the secondary battery is better. Preferably, 0.005≤c≤2.

[0014] In some embodiments, the secondary battery satisfies at least one of the following conditions: (1) the alloy element A includes Si, and the mass percentage of Si is 0.01% to 1% based on the mass of the positive electrode current collector; (2) the alloy element A includes Fe, and the mass percentage of Fe is 0.01% to 1% based on the mass of the positive electrode current collector; (3) the alloy element A includes Fe and Ti, and the mass percentage of Ti is less than the mass percentage of Fe based on the mass of the positive electrode current collector. Based on the above embodiments, if at least one of the above conditions is met, the secondary battery has better cycle performance.

[0015] In some embodiments, the electrolyte further includes a sulfur-oxygen double bond compound; the sulfur-oxygen double bond compound is selected from at least one of methane disulfonic acid methylene ester, 1,3-propane sultone, 1,4-butane sultone, propenyl-1,3-sultone, vinyl sulfate, 1,3-propane disulfonic anhydride, 2-methylbutane sultone or 1,3-propylene glycol cyclic sulfate; based on the mass of the electrolyte, the mass percentage of the sulfur-oxygen double bond compound is 0.01% to 5%. Based on the above embodiment, further adding a sulfur-oxygen double bond compound to the electrolyte and controlling the mass percentage within the above range can further inhibit the corrosion of the lithium salt in the electrolyte to the positive electrode current collector, so that the secondary battery has better rate performance and cycle performance.

[0016] In some embodiments, the electrolyte further contains a carbonate dimer, and the carbonate dimer is selected from the compound represented by the following formula (II):

[0017]

[0018] Wherein, R1 and R3 are independently selected from C1 to C4 alkyl groups, and R2 is selected from C1 to C4 alkylene groups; based on the total mass of the electrolyte, the mass percentage of the carbonate dimer is 0.001% to 5%. Based on the above embodiment, further adding the compound represented by formula (II) to the electrolyte and controlling the mass percentage within the above range can further inhibit the corrosion of the lithium salt in the electrolyte to the positive electrode current collector, so that the secondary battery has better rate performance and cycle performance.

[0019] In a second aspect, the present application provides an electronic device, comprising a secondary battery according to any embodiment of the first aspect.

[0020] According to the present application, since the electronic device includes the secondary battery described in any embodiment of the first aspect, it has the beneficial effects of the first aspect. DETAILED DESCRIPTION

[0021] The various embodiments or implementation schemes in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments.

[0022] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the implementation or examples are included in at least one implementation or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same implementation or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more implementations or examples in a suitable manner.

[0023] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0024] In the present application, the battery may include a lithium-ion secondary battery, a lithium-ion primary battery, a lithium-sulfur battery, a sodium-lithium-ion battery, a sodium-ion battery or a magnesium-ion battery, etc., and the embodiments of the present application do not limit this. The battery may be cylindrical, flat, rectangular or other shapes, etc., and the embodiments of the present application do not limit this.

[0025] In this specification, "alkyl" refers to a straight or branched saturated hydrocarbon group. "Alkenyl" refers to a straight or branched alkyl group containing one or more carbon to carbon double bonds. "Alkynyl" refers to a straight or branched alkyl group containing one or more carbon to carbon triple bonds. "Alkynyl" refers to a straight or branched alkyl group containing one or more carbon to carbon triple bonds. "Alkynyl" refers to a straight or branched saturated hydrocarbon group containing heteroatoms. "Aromatic" refers to an aromatic monocyclic hydrocarbon ring system or a polycyclic ring system in which two or more aromatic hydrocarbon rings are fused (i.e., contain a common bond) together or at least one aromatic monocyclic hydrocarbon ring is fused to one or more cycloalkyl and / or cycloheteroalkyl rings. "Sub" refers to a group that can form a covalent bond with two other parts.

[0026] In this specification, the substituents of compounds are disclosed in groups or ranges. It is explicitly expected that this description includes each individual subcombination of the members of these groups and ranges. For example, it is explicitly expected that the term "C1 to C6 alkyl" discloses C1, C2, C3, C4, C5, C6, C1 to C6, C1 to C5, C1 to C4, C1 to C3, C1 to C2, C2 to C6, C2 to C5, C2 to C4, C2 to C3, C3 to C6, C3 to C5, C3 to C4, C4 to C6, C4 to C5 and C5 to C6 alkyl individually.

[0027] Secondary battery

[0028] In a first aspect, the present application provides a secondary battery, comprising a positive electrode plate and an electrolyte, the positive electrode plate comprising a positive electrode collector and a positive electrode active material layer arranged on at least one surface of the positive electrode collector, wherein the positive electrode collector comprises a metal element Al and an alloy element A, the alloy element A comprises at least one of Fe, Si, Ti or V, and the mass percentage of the alloy element A is a%, 0.001≤a≤1 based on the mass of the positive electrode collector; the electrolyte comprises a lithium salt, the lithium salt comprises lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate, and the mass ratio of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate is b; a and b satisfy: 0.2≤b / a≤20000.

[0029] Based on the present application, the lithium salt in the electrolyte includes lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate. Lithium bis(fluorosulfonyl)imide can effectively improve the rate performance of the secondary battery, but a too high mass ratio of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate will cause corrosion to the positive electrode collector and deteriorate the cycle performance of the secondary battery. By doping a certain content of alloy element A in the positive electrode collector, the strength of the positive electrode collector can be effectively improved, and the influence of the lithium salt in the electrolyte on the positive electrode collector can be reduced. By controlling the mass ratio of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate in the lithium salt and the mass percentage of the alloy element A in the positive electrode collector to meet the above conditions, the secondary battery can have good cycle performance and rate performance.

[0030] Specifically, lithium bis(fluorosulfonyl)imide in the electrolyte is easily dissociated into lithium ions and bis(fluorosulfonyl)imide ions in the solvent due to its small molecule and strong ion dissociation ability, which can significantly improve the ionic conductivity of the electrolyte. However, bis(fluorosulfonyl)imide ions are easily decomposed at higher voltages to produce corrosive by-products (such as hydrogen fluoride, etc.), and the positive electrode collector is generally aluminum foil. The corrosive by-products have a strong corrosive effect on the positive electrode collector, causing the positive electrode collector to become thinner and the surface to oxidize, resulting in poor contact between it and the positive electrode active material layer, thereby reducing the effective utilization rate of the active material, and during the charge and discharge process, the active material gradually fails to have good contact with the positive electrode collector, resulting in a gradual decline in capacity, which reduces the overall performance of the secondary battery (especially the cycle performance). The present application reduces the concentration of bis(fluorosulfonyl)imide ions by mixing lithium bis(fluorosulfonyl)imide with lithium hexafluorophosphate as lithium salts, and at the same time, doping alloy element A in the positive electrode current collector can improve the strength of the positive electrode current collector, thereby reducing the influence of lithium bis(fluorosulfonyl)imide in the electrolyte on the positive electrode current collector; wherein, the mass percentage a of the alloy element A in the positive electrode current collector and the mass ratio b of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate satisfy the conditions of: 0.001≤a≤1, 0.2≤b / a≤20000, and the secondary battery can better balance the cycle performance and rate performance.

[0031] It can be understood that if the value of a is too small, the strength of the positive electrode current collector will not be significantly improved, and the influence of lithium bis(fluorosulfonyl)imide in the electrolyte on the positive electrode current collector cannot be effectively reduced. If the value of a is too high, it will affect the electrical properties of the positive electrode current collector; if the value of b / a is too small, the rate performance of the secondary battery cannot be significantly improved. If the value of b / a is too large, lithium bis(fluorosulfonyl)imide has a greater impact on the positive electrode current collector, which will affect the overall performance of the secondary battery. For example, the value of a can be 0.001, 0.067, 0.129, 0.171, 0.244, 0.354, 0.413, 0.513, 0.556, 0.630, 0.760, 0.831, 0.852, 0.946, 1, or a range consisting of any of the above values; the value of b / a can be 0.2, 1, 132, 981, 1958, 4292, 5081, 7508, 8471, 9647, 11547, 13066, 13920, 16436, 17328, 18758, 20000, or a range consisting of any of the above values.

[0032] In some embodiments, 2≤b / a≤4000. Based on the above embodiments, when b / a is within the above range, the secondary battery can better balance the cycle performance and rate performance.

[0033] In some embodiments, 0.005≤a≤0.5. Based on the above embodiments, when a is within the above range, the positive electrode current collector has a higher strength, the effect of lithium salt on the corrosion of the positive electrode current collector can be more effectively reduced, and the cycle performance of the secondary battery is better.

[0034] In some embodiments, 0.2≤b≤32. Based on the above embodiments, when b is within the above range, the rate performance of the secondary battery is better. For example, the value of b can be 0.2, 2.16, 3.13, 7.26, 7.88, 12.38, 14.07, 16.42, 18.47, 20.43, 24.64, 25.50, 28.64, 29.74, 32, or any of the above values.

[0035] In some embodiments, based on the mass of the electrolyte, the mass percentage of lithium bis(fluorosulfonyl)imide is 1% to 25%. For example, based on the mass of the electrolyte, the mass percentage of lithium bis(fluorosulfonyl)imide can be 1%, 1.6%, 2.8%, 3%, 4.2%, 5.0%, 6.9%, 7.6%, 8.5%, 10.7%, 12.0%, 13.3%, 14.0%, 15.0%, 16.7%, 17.9%, 19.4%, 20%, 21.5%, 23.6%, 24.3%, 25%, or within the range of any of the above values; preferably 3% to 20%.

[0036] In some embodiments, the electrolyte further comprises a compound represented by formula (I):

[0037]

[0038] Among them, R 11 The alkyl radical is selected from alkali metals, cyano, substituted or unsubstituted C1 to C6 alkyl, substituted or unsubstituted C2 to C6 alkenyl, substituted or unsubstituted C2 to C6 alkynyl, substituted or unsubstituted C1 to C6 heteroalkyl, the number of heteroatoms in the heteroalkyl is 1 to 5, the heteroatoms in the heteroalkyl are selected from O, N or S, and, when substituted, the substituent is selected from halogen atoms, cyano, C2 to C5 cycloalkyl or C6 to C 12 Aromatic base.

[0039] Based on the above embodiment, further adding the compound represented by formula (I) to the electrolyte can further inhibit the corrosion of the positive electrode current collector by the lithium salt in the electrolyte by forming a dense protective layer on the surface of the positive electrode current collector, thereby synergizing the alloy elements in the positive electrode current collector, further reducing the influence of the lithium salt in the electrolyte on the positive electrode current collector, and then appropriately increasing the mass ratio of lithium bis(fluorosulfonyl)imide to lithium hexafluorophosphate in the lithium salt, further improving the cycle performance and rate performance of the secondary battery.

[0040] It can also be understood that, in the compound represented by formula (I), the difluorophosphate group plays the above role in the electrolyte, wherein R 11 When the group is of the above type, the performance of the secondary battery will not be deteriorated. Some compounds represented by formula (I) are listed below as examples.

[0041] In some embodiments, the compound represented by formula (I) includes at least one of the following compounds:

[0042]

[0043]

[0044] Based on the above embodiments, the use of the above compounds can improve the cycle performance and rate performance of the secondary battery.

[0045] In some embodiments, based on the mass of the electrolyte, the mass percentage of the compound shown in formula (I) is c%, 0.04≤b / c≤20000. Based on the above embodiment, the mass percentage of the compound shown in formula (I) and the mass ratio of lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate in the electrolyte are controlled to satisfy the above relationship, which can further improve the cycle performance and rate performance of the secondary battery. For example, the value of b / c can be 0.04, 0.1, 0.5, 1, 15, 200, 453, 2058, 3660, 5372, 7349, 8605, 10053, 11140, 13260, 14315, 16497, 17658, 18727, 20000, or within the range of any of the above values. Preferably 2≤b / c≤4000.

[0046] In some embodiments, 0.001≤c≤5. Based on the above embodiments, when the mass percentage of the compound represented by formula (I) satisfies the above range, the cycle performance of the secondary battery is better. For example, the value of c can be 0.001, 0.12, 0.72, 0.98, 1.45, 1.78, 2.17, 2.52, 2.95, 3.35, 3.76, 4.13, 4.28, 4.90, 5, or within the range of any of the above values. Preferably, 0.005≤c≤2.

[0047] In some embodiments, the alloy element A includes Si, and the mass percentage of Si is 0.01% to 1% based on the mass of the positive electrode collector. Based on the above embodiment, doping with the Si element with the above mass percentage can further improve the strength of the positive electrode collector without affecting the electrical properties of the positive electrode collector, and further improve the cycle performance of the secondary battery. For example, the mass percentage of Si can be 0.01%, 0.03%, 0.12%, 0.17%, 0.28%, 0.39%, 0.41%, 0.53%, 0.58%, 0.66%, 0.73%, 0.85%, 0.91%, 0.97%, 1%, or within the range of any of the above values.

[0048] In some embodiments, the alloy element A includes Fe, and the mass percentage of Fe is 0.01% to 1% based on the mass of the positive electrode collector. Based on the above embodiment, doping with the above mass percentage of iron can further improve the strength of the positive electrode collector without affecting the electrical properties of the positive electrode collector, and further improve the cycle performance of the secondary battery. For example, the mass percentage of Fe can be 0.01%, 0.03%, 0.12%, 0.17%, 0.28%, 0.39%, 0.41%, 0.53%, 0.58%, 0.66%, 0.73%, 0.85%, 0.91%, 0.97%, 1%, or within the range of any of the above values.

[0049] In some embodiments, the alloy element A includes Fe and Ti, and the mass percentage of Ti is less than the mass percentage of Fe based on the mass of the positive electrode current collector. Based on the above embodiment, using Fe and Ti as alloy elements can further improve the strength of the positive electrode current collector. At the same time, since the conductivity of Ti is relatively poor compared to Al and Fe, controlling the mass percentage of Ti to be less than the mass percentage of Fe can reduce the impact on the electrical properties of the positive electrode current collector, so that the secondary battery has better cycle performance.

[0050] In some embodiments, the electrolyte further includes a sulfur-oxygen double bond compound; the sulfur-oxygen double bond compound is selected from at least one of methane disulfonic acid methylene ester, 1,3-propane sultone, 1,4-butane sultone, propenyl-1,3-sultone, vinyl sulfate, 1,3-propane disulfonic anhydride, 2-methylbutane sultone or 1,3-propylene glycol cyclic sulfate; based on the mass of the electrolyte, the mass percentage of the sulfur-oxygen double bond compound is 0.01% to 5%. Based on the above embodiment, further adding a sulfur-oxygen double bond compound to the electrolyte and controlling the mass percentage within the above range can further inhibit the corrosion of the lithium salt in the electrolyte to the positive electrode current collector, so that the secondary battery has better rate performance and cycle performance. For example, the mass percentage of the sulfur-oxygen double bond compound can be 0.01%, 0.17%, 0.57%, 0.83%, 1.41%, 1.65%, 1.96%, 2.60%, 2.97%, 3.28%, 3.68%, 4.06%, 4.28%, 4.86%, 5%, or any range composed of the above values.

[0051] In some embodiments, the electrolyte further contains a carbonate dimer, and the carbonate dimer is selected from the compound represented by the following formula (II):

[0052]

[0053] Wherein, R1 and R3 are independently selected from alkyl groups of C1 to C4, and R2 is selected from alkylene groups of carbon atoms of C1 to C4; based on the total mass of the electrolyte, the mass percentage of the carbonate dimer is 0.001% to 5%. Based on the above embodiment, further adding the compound represented by formula (II) to the electrolyte and controlling the mass percentage within the above range can further inhibit the corrosion of the positive electrode collector by the lithium salt in the electrolyte, so that the secondary battery has better rate performance and cycle performance. For example, the mass percentage of the carbonate dimer can be 0.001%, 0.01%, 0.06%, 0.48%, 0.84%, 1.48%, 1.61%, 2.00%, 2.58%, 2.95%, 3.40%, 3.53%, 4.04%, 4.52%, %, 4.89%, 5%, or within the range composed of any of the above values.

[0054] In some embodiments, the compound represented by formula (II) includes at least one of the following compounds:

[0055]

[0056] In some embodiments, the electrolyte further includes an organic solvent, and the organic solvent includes but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS) and diethyl sulfone (ESE).

[0057] The positive electrode active material layer contains a positive electrode active material, and the positive electrode active material layer can be one layer or multiple layers. Each layer in the multiple layers of positive electrode active material layers can contain the same or different positive electrode active materials. The positive electrode active material is any material that can reversibly intercalate and deintercalate alkali metal ions.

[0058] The positive electrode active material includes a lithium transition metal oxide containing nickel and other transition metals. In the lithium transition metal oxide including nickel and other transition metals, the amount of nickel relative to the total molar number of the transition metal may be 60 mol% or more, for example, 75 mol% or more, for example, 80 mol% or more, for example, 85 mol% or more, or for example, 90 mol% or more.

[0059] In some embodiments, the positive electrode active material includes at least one active material selected from the group consisting of lithium nickel cobalt manganese oxide (NCM), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide, lithium manganese oxide, or lithium iron manganese phosphate.

[0060] In some embodiments, the positive electrode active material layer includes a positive electrode conductive material; the type of the positive electrode conductive material is not limited, and any known conductive material can be used. Examples of positive electrode conductive materials may include, but are not limited to, carbon black such as acetylene black and Super-P; amorphous carbon materials such as needle coke; carbon nanotubes; graphene, etc. The above positive electrode conductive materials may be used alone or in any combination.

[0061] In some embodiments, the positive electrode active material layer includes a positive electrode binder. The type of the positive electrode binder is not particularly limited, and in the case of a coating method, it can be any material that is soluble or dispersible in a liquid medium used in electrode manufacturing. Examples of positive electrode binders may include, but are not limited to, one or more of the following: resin-based polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose or nitrocellulose; rubber-like polymers such as styrene-butadiene rubber (SBR), nitrile rubber (NBR), fluororubber, isoprene rubber, polybutadiene rubber or ethylene-propylene rubber; thermoplastic elastomer-like polymers such as styrene-butadiene-styrene block copolymer or its hydride, ethylene-propylene-diene terpolymer (EPDM), styrene-ethylene-butadiene-ethylene copolymer, styrene-isoprene-styrene block copolymer or its hydride; soft resin-like polymers such as syndiotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymer or propylene-α-olefin copolymer; fluorine-based polymers such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene, fluorinated polyvinylidene fluoride or polytetrafluoroethylene-ethylene copolymer; polymer compositions having ionic conductivity of alkali metal ions, etc. The above positive electrode binders may be used alone or in any combination.

[0062] There is no limitation on the type of solvent used to form the positive electrode slurry, as long as it is a solvent that can dissolve or disperse the positive electrode active material, the conductive material, the positive electrode binder, and the thickener used as needed. Examples of solvents used to form the positive electrode slurry may include any of aqueous solvents and organic solvents. Examples of aqueous media may include, but are not limited to, a mixed medium of alcohol and water or water, etc. Examples of organic media may include, but are not limited to, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran; amides such as N-methylpyrrolidone, dimethylformamide, and dimethylacetamide; non-protonic polar solvents such as hexamethylphosphoramide or dimethyl sulfoxide, etc.

[0063] The thickener is usually used to adjust the viscosity of the slurry. In the case of using an aqueous medium, the thickener and styrene-butadiene rubber emulsion can be used for slurrying. The type of thickener is not particularly limited, and examples thereof may include, but are not limited to, carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch or casein and their salts, etc. The above thickeners may be used alone or in any combination.

[0064]

Negative electrode

[0065] The secondary battery also includes a negative electrode sheet, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material. In some embodiments, the chargeable capacity of the negative electrode active material is greater than the discharge capacity of the positive electrode active material to prevent lithium metal from being accidentally precipitated on the negative electrode during charging.

[0066] The negative electrode active material may include natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), silicon, silicon-carbon composites, SiO x (0.5<x<1.6), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structure lithium titanate Li4Ti5O 12 , Li-Al alloy or metallic lithium, etc. Optionally, the negative electrode active material may further include an amorphous carbon material, and the amorphous carbon may be soft carbon (low temperature calcined carbon), hard carbon, mesophase pitch carbide or calcined coke, etc.

[0067] The negative electrode active material layer of the present application also includes a negative electrode binder. The negative electrode binder can improve the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector. The type of negative electrode binder is not particularly limited, as long as it is a material that is stable to the solvent used in the manufacture of the electrolyte or electrode. In some embodiments, the negative electrode binder includes a resin binder. Examples of resin binders include, but are not limited to, fluororesins, polyacrylonitrile (PAN), polyimide resins, acrylic resins, polyolefin resins, and the like. When an aqueous solvent is used to prepare the negative electrode mixture slurry, the negative electrode binder includes, but is not limited to, carboxymethyl cellulose (CMC) or its salt, styrene-butadiene rubber (SBR), polyacrylic acid (PAA) or its salt, polyvinyl alcohol, and the like.

[0068] The negative electrode active material layer of the present application also includes a conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent, as long as the purpose of the present application can be achieved. For example, the negative electrode conductive agent can be at least one of acetylene black, Ketjen black, carbon nanotubes, carbon fibers, carbon dots or graphene, and the above-mentioned carbon nanotubes can include but are not limited to at least one of single-walled carbon nanotubes or multi-walled carbon nanotubes.

[0069] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the negative electrode current collector may include copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a polymer substrate covered with a conductive metal, etc. Among them, the conductive metal includes but is not limited to copper, nickel or titanium, and the material of the polymer substrate includes but is not limited to at least one of polyethylene, polypropylene, ethylene propylene copolymer, polyethylene terephthalate, polyethylene naphthalate or poly(p-phenylene terephthalamide). In the present application, there is no particular restriction on the thickness of the negative electrode current collector and the negative electrode active layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4μm to 12μm, and the thickness of the single-sided negative electrode active layer is 30μm to 160μm. In the present application, the negative electrode active layer can be arranged on one surface in the thickness direction of the negative electrode current collector, or on two surfaces in the thickness direction of the negative electrode current collector. It should be noted that the "surface" here can be the entire area of ​​the negative electrode current collector or a partial area of ​​the negative electrode current collector. This application has no special restrictions as long as the purpose of this application can be achieved.

[0070] The present application has no particular restrictions on the compaction density of the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the compaction density of the negative electrode sheet can be 1.0 g / cm 3 Up to 1.85g / cm 3 The present application has no particular limitation on the cold pressing pressure of the negative electrode plate, as long as the purpose of the present application can be achieved. For example, the cold pressing pressure of the negative electrode plate can be 3 tons to 30 tons.

[0071] Optionally, the negative electrode plate may further include a conductive layer, which is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, which may be a conductive layer commonly used in the art. The conductive layer includes a conductive agent and a binder. The present application has no particular restrictions on the conductive agent and the binder in the conductive layer, which may be at least one of the above conductive agent and the above binder. The present application has no particular restrictions on the mass ratio of the conductive agent and the binder in the conductive layer, and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. The present application has no particular restrictions on the thickness of the conductive layer, as long as the purpose of the present application can be achieved, for example, the thickness of the conductive layer is 1μm to 10μm.

[0072]

Isolation film

[0073] In the present application, a separator is usually provided between the positive electrode sheet and the negative electrode sheet. The separator is used to separate the positive electrode sheet and the negative electrode sheet, prevent the internal short circuit of the secondary battery, allow the electrolyte ions to pass freely, and do not affect the electrochemical charge and discharge process.

[0074] The present application has no particular restrictions on the isolation membrane, as long as the purpose of the present application can be achieved. For example, the material of the isolation membrane may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyester (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid; the type of isolation membrane may include at least one of woven membrane, non-woven membrane, microporous membrane, composite membrane, rolled membrane or spun membrane.

[0075] In the present application, the isolation membrane may include a substrate and a surface treatment layer. The substrate may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. For example, the inorganic layer includes inorganic particles and a binder, and the present application has no particular restrictions on the above-mentioned inorganic particles, for example, it may include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the above-mentioned binder, for example, it may be at least one of the aforementioned binders. The polymer layer contains a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or poly(vinylidene fluoride-hexafluoropropylene).

[0076] The pore size of the isolation membrane in the present application is 0.01 μm to 1 μm, and the thickness is 5 μm to 50 μm. In some embodiments, the thickness of the isolation membrane is greater than 5 μm or greater than 8 μm. In some embodiments, the thickness of the isolation membrane is less than 50 μm, less than 40 μm, or less than 30 μm. When the thickness of the isolation membrane is within the above range, the insulation and mechanical strength can be ensured, and the rate characteristics and energy density of the secondary battery can be ensured.

[0077] The electrochemical device of the present application also includes a packaging bag for containing a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the art in the electrochemical device, and the present application does not limit the above other components. The present application does not specifically limit the packaging bag, and it can be a packaging bag known in the art, as long as it can achieve the purpose of the present application.

[0078] Electronic devices

[0079] In a second aspect, the present application provides an electronic device, comprising a secondary battery according to any embodiment of the first aspect.

[0080] According to the present application, since the electronic device includes the secondary battery of any embodiment of the first aspect, it has the beneficial effects of the first aspect.

[0081] The electronic device of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device can include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0082] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0083] <Test method>

[0084] (1) Test of Al content on negative electrode after storage:

[0085] Place the lithium-ion battery in a constant temperature box at 25°C, let it stand for 30 minutes, charge it to 4.2V at a constant current rate of 1C, then charge it at constant voltage until the current is less than or equal to 0.05C, then let it stand for 5 minutes, discharge it to 2.8V at a constant current rate of 1C, then charge it to 4.2V at a constant current rate of 1C, charge it at constant voltage until the current is less than or equal to 0.05C, and then place the fully charged lithium-ion battery in a 60°C oven for storage for 90 days.

[0086] The stored lithium-ion batteries are disassembled to obtain negative electrode sheets. Any position of the negative electrode sheets is randomly selected to obtain negative electrode sheets of a certain size. The negative electrode sheets are digested with acid to form a solution. The solution is atomized and then subjected to inductively coupled plasma (ICP) testing to obtain the content of Al element in the negative electrode active material.

[0087] (2) Rate performance test:

[0088] Place the lithium-ion battery in a 25°C constant temperature box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge the lithium-ion battery that has reached a constant temperature at a constant current of 1C to a voltage of 4.2V, and then charge it at a constant voltage of 4.2V to a current of less than or equal to 0.05C. Subsequently, discharge it at a constant current of 1C and 5C to 2.8V, respectively, to obtain the 1C discharge capacity and 5C discharge capacity of the lithium-ion battery. Divide the 5C discharge capacity by the 1C discharge capacity to obtain the 5C capacity retention rate.

[0089] Example 1

[0090] (1) Preparation of negative electrode: Mix the negative electrode active material artificial graphite, the conductive agent Super P, and the negative electrode binder sodium carboxymethyl cellulose in a mass ratio of 96:2:2, add deionized water and stir evenly to obtain a negative electrode slurry with a solid content of 70wt%. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 8μm, and then dried at 110°C. The above steps are repeated on the other surface of the negative electrode current collector. After cold pressing, a double-sided coated negative electrode sheet with a single-sided negative electrode material layer thickness of 150μm is obtained. The compaction density of the single-sided negative electrode material layer is 1.6g / cm 3 Then the negative electrode sheet is die-cut into a negative electrode sheet with two or more negative electrode tabs on one side of the negative electrode collector and a specification of 78mm×875mm.

[0091] (2) Preparation of positive electrode: The positive electrode active material LiMn2O4, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 96:2:2, and N-methylpyrrolidone (NMP) was added as a solvent. The system was stirred under the action of a vacuum mixer until the system became a uniform positive electrode slurry with a solid content of 75wt%. The positive electrode slurry was evenly coated on a positive electrode collector with a thickness of 12μm, wherein the element composition of the positive electrode collector was: the mass percentage content a of the alloy element A was 0.001%, the alloy element A was Fe, and the remainder was Al; dried at 85°C, and the above steps were repeated on the other surface of the positive electrode collector. After cold pressing, a double-sided coated positive electrode sheet with a thickness of 100μm was obtained. The positive electrode sheet was die-cut into a positive electrode sheet with two or more positive electrode tabs on one side of the positive electrode collector and a specification of 74mm×867mm.

[0092] (3) Preparation of electrolyte: In an argon atmosphere glove box with a water content of <10 ppm, organic solvents ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) were mixed uniformly at a mass ratio of 1:1:3 to obtain a base solvent. Fully dried lithium bis(fluorosulfonyl)imide, lithium hexafluorophosphate, sulfur-oxygen double bond compound and carbonate dimer were dissolved in the above base solvent and mixed uniformly to obtain an electrolyte, wherein the mass percentage of lithium bis(fluorosulfonyl)imide was 12%, the mass percentage of lithium hexafluorophosphate was 0.6%, the types of sulfur-oxygen double bond compound and carbonate dimer and their mass percentages are shown in Table 1, and the remainder is the base solvent.

[0093] (4) Preparation of isolation membrane: A polyethylene (PE) porous polymer film is used as the isolation membrane.

[0094] (5) Preparation of lithium-ion battery: The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in order, with the separator placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain an electrode assembly. The electrode assembly is placed in an aluminum-plastic film packaging bag, placed in a vacuum oven at 85°C to dry for 12 hours to remove moisture, and the prepared electrolyte is injected. After vacuum packaging, standing, formation, shaping, capacity testing, secondary packaging and other processes, a lithium-ion battery is obtained.

[0095] The Al element content on the negative electrode and the rate performance test were performed on the lithium-ion battery after storage. The results are shown in Table 1.

[0096] Examples 1 to 42, Comparative Example 1

[0097] Except for adjusting the parameters according to Table 1, the rest is the same as Example 1-1.

[0098] The Al element content on the negative electrode and the rate performance test were performed on the above lithium-ion batteries after storage. The results are shown in Table 1.

[0099]

[0100]

[0101]

[0102]

[0103] According to Table 1, compared with Comparative Example 1, each embodiment has a lower Al element content on the negative electrode after storage and a higher 5C capacity retention rate, wherein the Al element content on the negative electrode after storage is derived from the corrosion of the electrolyte on the positive electrode current collector. The lower the Al element content, the better the stability of the positive electrode current collector, and the better the cycle performance of the response battery. A higher 5C capacity retention rate indicates that the battery has better rate performance, that is, by doping the positive electrode current collector with alloy elements and controlling the composition of the lithium salt in the electrolyte, and satisfying the conditions of 0.001≤a≤1, 0.2≤b / a≤20000, the battery has better cycle performance and rate performance.

[0104] Further, according to Examples 1, 3 to 10, and 12 to 17, it can be known that under the condition of 2≤b / a≤4000, the battery can better balance the cycle performance and the rate performance; under the condition of 0.005≤a≤0.5, the battery can better balance the cycle performance and the rate performance; under the condition of 0.2≤b≤32, the battery can better balance the cycle performance and the rate performance; under the condition that the mass percentage of lithium bis(fluorosulfonyl)imide in the electrolyte is 3% to 20%, the battery can better balance the cycle performance and the rate performance.

[0105] According to Examples 2, 7, 11, 18 to 23, and 28 to 32, further adding the compound represented by formula (I) to the electrolyte can synergistically dope the positive electrode current collector with alloy elements to further improve the cycle performance and rate performance of the battery; and under the conditions of 2≤b / c≤4000 and / or 0.005≤c≤2, the cycle performance and rate performance of the battery are better.

[0106] According to Examples 7, 24 to 27, it can be seen that by doping different alloy elements A in the positive electrode current collector and controlling the mass percentage of the alloy element A in the positive electrode current collector to 0.001% to 1%, the cycle performance and rate performance of the battery can be improved. Among them, when the positive electrode current collector is doped with Si, the cycle performance and rate performance of the battery are better.

[0107] According to Examples 7, 33 to 37, further adding a sulfur-oxygen double bond compound into the electrolyte can further improve the cycle performance and rate performance of the battery.

[0108] According to Examples 7, 38 to 42, further adding a carbonate-containing dimer into the electrolyte can further improve the cycle performance and rate performance of the battery.

[0109] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A secondary battery, characterized in that: Including positive electrode and electrolyte, The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode current collector comprises a metal element Al and an alloy element A, the alloy element A comprises at least one of Fe, Si, Ti or V, and the mass percentage of the alloy element A is a%, 0.001≤a≤1, based on the mass of the positive electrode current collector; The electrolyte includes a lithium salt, wherein the lithium salt includes lithium bis(fluorosulfonyl)imide and lithium hexafluorophosphate, and the mass ratio of the lithium bis(fluorosulfonyl)imide to the lithium hexafluorophosphate is b; The a and b satisfy: 0.2≤b / a≤20000.

2. The secondary battery according to claim 1, characterized in that: The secondary battery satisfies at least one of the following conditions: (1)2≤b / a≤4000; (2)0.005≤a≤0.5; (3)0.2≤b≤32; (4) Based on the mass of the electrolyte, the mass percentage of the bis(fluorosulfonyl)imide lithium is 1% to 25%.

3. The secondary battery according to claim 1, characterized in that: The electrolyte also includes a compound represented by formula (I): Among them, R 11 The alkyl radical is selected from alkali metals, cyano groups, substituted or unsubstituted C1 to C6 alkyl groups, substituted or unsubstituted C2 to C6 alkenyl groups, substituted or unsubstituted C2 to C6 alkynyl groups, substituted or unsubstituted C1 to C6 heteroalkyl groups, wherein the number of heteroatoms in the heteroalkyl group is 1 to 5, wherein the heteroatoms in the heteroalkyl group are selected from O, N or S, and, when substituted, the substituent is selected from halogen atoms, cyano groups, C2 to C5 cycloalkyl groups or C6 to C 12 Aromatic base.

4. The secondary battery according to claim 3, characterized in that: The compound represented by formula (I) includes at least one of the following compounds:

5. The secondary battery according to claim 3 or 4, characterized in that: Based on the mass of the electrolyte, the mass percentage of the compound represented by formula (I) is c%, and 0.04≤b / c≤20000.

6. The secondary battery according to claim 5, characterized in that: 0.001≤c≤5。 7. The secondary battery according to claim 1, characterized in that: The secondary battery satisfies at least one of the following conditions: (1) The alloy element A includes Si, and the mass percentage of Si is 0.01% to 1% based on the mass of the positive electrode current collector; (2) the alloy element A includes Fe, and the mass percentage of Fe is 0.01% to 1% based on the mass of the positive electrode current collector; or (3) The alloy element A includes Fe and Ti, and the mass percentage of the Ti is less than the mass percentage of the Fe based on the mass of the positive electrode current collector.

8. The secondary battery according to claim 1, characterized in that: The electrolyte further comprises a sulfur-oxygen double bond compound; the sulfur-oxygen double bond compound is selected from at least one of methanedisulfonic acid methylene ester, 1,3-propane sultone, 1,4-butane sultone, propenyl-1,3-sultone, vinyl sulfate, 1,3-propanedisulfonic anhydride, 2-methylbutane sultone or 1,3-propylene glycol cyclic sulfate; Based on the mass of the electrolyte, the mass percentage of the sulfur-oxygen double bond compound is 0.01% to 5%.

9. The secondary battery according to claim 1, characterized in that: The electrolyte further contains a carbonate dimer, and the carbonate dimer is selected from the compound represented by the following formula (II): Wherein, R1 and R3 are independently selected from C1 to C4 alkyl groups, and R2 is selected from C1 to C4 alkylene groups; Based on the total mass of the electrolyte, the mass percentage of the carbonate dimer is 0.001% to 5%.

10. An electronic device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 9.